Bacterial synthesis of copper/copper oxide nanoparticles - Hasan, Syed Saif; Singh, Sanjay; Parikh, Rasesh Y.; Dharne, Mahesh S.; Patole, Milind S.; Bhagavatula L. V. Prasad; Shouche, Yogesh S. (Journal of Nanoscience and Nanotechnology, 2008)
A bacterial mediated synthesis of copper/copper oxide nanoparticle composite is reported. A Gram-negative bacterium belonging to the genus Serratia was isolated from the midgut of Stibara sp., an insect of the Cerambycidae family of beetles found in the Northwestern Ghats of India. This is a unique bacterium that is quite specific for the synthesis of copper oxide nanoparticles as several other strains isolated from the same insect and common Indian mosquitoes did not result in nanoparticle formation. By following the reaction systematically, we could delineate that the nanoparticle formation occurs intracellularly. However, the process results in the killing of bacterial cells. Subsequently the nanoparticles leak out as the cell wall disintegrates. The nanoparticles formed are thoroughly characterized by UV-Vis, TEM, XRD, XPS and FTIR studies.
Keywords: bacterial synthesis; Nanoparticles; TEM; XPS; XRD

Bacteria-mediated precursor-dependent biosynthesis of superparamagnetic iron oxide and iron sulfide nanoparticles - Bharde, Atul A.; Parikh, Rasesh Y.; Baidakova, Marina; Jouen, Samuel; Hannoyer, Beatrice; Enoki, Toshiaki; Bhagavatula L. V. Prasad; Shouche, Yogesh S.; Ogale, Satishchandra B.; Sastry, Murali (Langmuir, 2008)
The bacterium Actinobacter sp. has been shown to be capable of extracellularly synthesizing iron based magnetic nanoparticles, namely maghemite (gamma-Fe2O3) and greigite (Fe3S4) Under ambient conditions depending on the nature of precursors used. More precisely, the bacterium synthesized maghemite when reacted with ferric chloride and iron sulfide when exposed to the aqueous solution of ferric chloride-ferrous sulfate. Challenging the bacterium with different metal ions resulted in induction of different proteins, which bring about the specific biochemical transformations in each case leading to the observed products. Maghemite and iron sulfide nanoparticles show superparamagnetic characteristics as expected. Compared to the earlier reports of magnetite and greigite synthesis by magnetotactic bacteria and iron reducing bacteria, which take place strictly under anaerobic conditions, the present procedure offers significant advancement since the reaction occurs under aerobic condition. Moreover, reaction end products can be tuned by the choice of precursors used.

Bacillus enclensis sp nov., isolated from sediment sample - Dastager, Syed Gulam; Mawlankar, Rahul R.; Tang, Shan-Kun; Srinivasan, Krishnamurthi; Ramana, V. Venkata; Shouche, Yogesh S. (Antonie Van Leeuwenhoek International Journal of General and Molecular Microbiology, 2014)
A novel bacterial strain, designated SGD-1123(T) was isolated from Chorao Island, in Goa Province, India. The strain was found to be able to grow at 15-42 A degrees C, pH 5-12 and 0-12 % (w/v) NaCl. The whole cell hydrolysates were found to contain meso-diaminopimelic acid, galactose and arabinose. The major fatty acids were identified as iso-C-15:0 and anteiso-C-15:0, MK-7 was identified as the predominant menaquinone and the predominant polar lipids were identified as diphosphatidylglycerol, phosphatidylglycerol, phosphatidylethanolamine and an unidentified aminolipid. The genomic DNA G+C content was determined to be 44.6 mol%. Phylogenetic analysis based on 16S rRNA gene sequences placed the isolate within the genus Bacillus and further revealed that strain SGD-1123(T) had highest sequence similarity with Bacillus aquimaris, and forms a separate clade with its closest relatives i.e. B. aquimaris, Bacillus vietnamensis and Bacillus marisflavi, with which it shares 94.5, 94.1 and 94.1 % similarity respectively. The phylogenetic, chemotaxonomic and phenotypic analyses indicated that strain SGD-1123(T) represents a novel species within the genus Bacillus, for which the name Bacillus enclensis is proposed. The type strain is SGD-1123(T) (NCIM 5450(T)=CCTCC AB 2011125(T)).
Keywords: Bacillus sp; Marine sediment; Polyphasic

Bacillus encimensis sp nov isolated from marine sediment - Dastager, Syed Gulam; Mawlankar, Rahul R.; Mual, Poonam; Verma, Ashish; Krishnamurthi, Srinivasan; Joseph, Neeta; Shouche, Yogesh S. (International Journal of Systematic and Evolutionary Microbiology, 2015)
A Gram-stain-positive, rod-shaped, endospore-forming, aerobic bacterium designated SGD-V-25(T) was isolated from Veraval sediment sample, India. Strain SGD-V-25(T) was capable of growing at 25-50 degrees C (optimum 37 degrees C), pH 6-12 (optimum pH 7.0) and with 0-5 % (w/v) NaCl. The taxonomic position of this strain was deduced using a polyphasic approach and the 16S rRNA gene sequence analysis showed that the isolate belongs to the phylum Firmicutes, forming the cluster with Bacillus badius MTCC 1548(T), with which it shares highest similarity of 99.1 % with 13 nt differences. Other type strains of the genus Bacillus showed less than 96% similarity. The cell wall contained meso-diaminopimelic acid as the diagnostic diamino acid. The polar lipid profile of strain SGD-V-25(T) showed the presence of diphosphatidylglycerol, phosphatidylglycerol, phsophoglycolipid and two aminophospholipids. The predominant isoprenoid quinone was MK-7. The major cellular fatty acids were iso-C-15:0, anteiso-C-15:0, anteiso-C-17:0 iso-C-16:0, C-16:1 omega 11c and C-16:0. The genomic DNA G + C content of strain SGD-V-25(T) was 37.6 molok. On the basis of phenotypic characteristics, phylogenetic analysis and DNA-DNA hybridization, strain SGD-V-25(T) could be clearly distinguished from closely related members of the genus Bacillus, and the name Bacillus encimensis sp. nov., is proposed to accommodate this strain. The type strain is SGD-V-25(T) (= NCIM 5513(T)=DSM 28241(T)).

Bacillus filamentosus sp nov., isolated from sediment sample - Sonalkar, Vidya V.; Mawlankar, Rahul R.; Ramana, V. Venkata; Joseph, Neeta; Shouche, Yogesh S.; Dastager, Syed Gulam (Antonie Van Leeuwenhoek International Journal of General and Molecular Microbiology, 2015)
A novel Gram-stain positive, endospore-forming bacterium, designated SGD-14(T), was isolated from a marine sediment sample in Goa Province, India. Cells of the isolate were found to be strictly aerobic. Phylogenetic analysis based on 16S rRNA gene sequences indicated that strain SGD-14(T) showed a similarity of 99.5 % with Bacillus endophyticus and similarities to other Bacillus type strains were below 96 %. The whole-cell sugar pattern was found to consist of ribose, xylose and glucose. The predominant menaquinone was identified as MK-7 and the major fatty acids as anteiso-C-15:0, iso-C-15:0, iso-C-16:0, anteiso-C-17:0, C-16:0 and iso-C-14:0. The strain was found to grow optimally at 30 A degrees C and pH 7.0-7.5. DNA G + C content was determined to be 39.6 mol%. The phospholipid pattern was found to consist of diphosphatidylglycerol, phosphatidylglycerol and phosphatidylethanolamine. DNA-DNA hybridization studies between strain SGD-14(T) and B. endophyticus CIP106778(T) showed that strain SGD-14(T) exhibited < 70 % similarity with B. endophyticus CIP106778(T). Differences in phenotypic and chemotaxonomic characteristics between the novel strain and B. endophyticus CIP106778(T) further confirmed that this isolate represents novel species. Phylogenetic analysis showed that strain SGD-14(T) fits in the same clade with B. endophyticus with 100 % bootstrap values. Strain SGD-14(T) is therefore considered to represent a novel species of the genus Bacillus, for which the name Bacillus filamentosus sp. nov. is proposed. The type strain of Bacillus filamentosus is SGD-14(T) = (=NCIM 5491(T) = DSM 27955(T)).
Keywords: Bacillus; Filaments; Polyphasic; Sediment